In vitro assessment on the ability of a novel lipopolysaccharide binding compound (EVK063) to inhibit cytokine production in LPS-stimulated equine peripheral blood mononuclear cells - Jones, Phillip D. (Kansas State University, 2009)
Objective: To assess the in vitro ability of a novel lipopolysaccharide binding compound (EVK063) to inhibit cytokine production in lipopolysaccharide-stimulated equine peripheral blood mononuclear cells Animals: Eight healthy horses were sources for mononuclear cells. Procedures: Replicate aliquots (concentrated at 4-5 million cells/mL) were stimulated with S. typhimurium lipopolysaccharide (LPS) (100ng/mL), treated with graded concentrations of EVK063, (0.01µM, 0.1µM, 1µM, 10µM), Polymyxin B (PMB) (10µM) and incubated at 37°C for 6 hours. Media and cell samples were collected and stored at -80°C for evaluation of Tumor necrosis factor (TNF) using an equine specific ELISA and Interleukin-6 (IL6) via qRT-PCR. NanoDrop confirmed RNA quantity and primer sets designed for equine IL6 and the housekeeping gene 18s were used. EVK063 toxicity was evaluated with propidium iodide staining as determined by flow cytometry. Data was normalized, expressed as percent inhibition of cytokine up-regulation by LPS, and statistically evaluated by analysis of variance. Statistical significance was set at P ≤ 0.05. Results: Samples incubated in media with 0% serum demonstrated the following results: 0.01µM and 0.1µM EVK063 maintained >90% cellular viability yet failed to significantly inhibit TNF production or IL6 expression. The 1µM and 10µM EVK063 concentrations exhibited 25% and 70% cell death respectfully and therefore an interpretation as to their efficacy to inhibit TNF production or IL6 expression could not be made. Samples incubated in media with 10% serum demonstrated the following results: 0.01µM, 0.1µM and 1µM concentrations of EVK063 maintained >90% cellular viability yet failed to inhibit TNF production or IL6 expression. The 10µM EVK063 concentration exhibited 35% cell death and therefore an interpretation as to the efficacy to inhibit TNF production or IL6 expression could not be made. In a whole blood preparation, all samples evaluated maintained >90% cellular viability. The 10µM EVK063 significantly reduced TNF production and IL6 expression. Conclusion: This in vitro study confirms the ability of EVK063 to inhibit TNF production and IL6 expression in LPS stimulated equine mononuclear cells with comparable results to PMB.
Keywords: Equine; Endotoxin; Il-6; Therapy; PCR; Elisa; Agriculture, Animal Pathology (0476)